National statuses granted for protection reasons in Ireland - Sarah Groarke; Patricia Brazil (The Economic and Social Research Institute (ESRI), 2020)
Ireland has increased pathways to protection for people fleeing persecution or harm. However, this study, conducted by researchers in EMN Ireland, shows that disparities in supports remain. The new study examines how increased numbers of migrants in need of protection have been offered residence in Ireland under national law and new resettlement schemes, which give the State more flexibility to respond to growing protection needs. The research highlights disparities in supports and entitlements among different groups of status-holders, such as more limited access to education and employment.
Keywords: 330; Asylrecht; Migrationspolitik; EU-Recht; Irland